بیسویں صدی میں الجزائر کا سماجی و سیاسی پس منظر،افکارِ مالک بن نبیؒ کے تناظرمیں جائزہ: Social and Political Background of 20th Century Algeria in The Context of Malik Bennabi's Thoughts - Dr. Samiul Haq; Hafiz Ehsan Ullah Habib; Iftikhar Ahmad (Al Manhal Research Journal, 2024)
When Malik Bennabi was born, Algeria was under French occupation. He was born in 1905, during a period when France's colonial rule lasted from 1830 to 1962. Prior to this, France and Algeria had friendly relations. Algeria had established diplomatic relations with various countries, and in 1564, the first French ambassador was appointed in Algeria. In the early 19th century, France faced severe economic problems and sought help from Algeria. Consequently, Algeria provided wheat and other commodities on credit. Later, France delayed repayment, and using various pretexts, launched a military invasion of Algeria. Simultaneously, efforts were made to fully assimilate Algeria into French civilization, which was pursued on four fronts. In this context, Malik Bennabi's educational, cultural, and colonial studies perceived the situation. He wrote about the causes, highlighted the issues, exposed all the tactics of colonialism, and proposed a course of action and simple solutions. The discussed article will mention the conditions under which Malik Bennabi's intellectual and ideological growth occurred and how he played a foundational role in Algeria's military and cultural freedom.